“Somewhere I belong?” A study on transnational identity shifts caused by “double stigmatization” among Chinese international student returnees during COVID-19 through the lens of mindsponge mechanism - Jin, Ruining; Wang, Xiao (Frontiers in Psychology, 2022)
Chinese international students who studied in the United States received “double stigmatization” from American and Chinese authorities because of the “political othering” tactic during COVID-19. The research used a phenomenological study to examine why and how specifically the transnational identity of Chinese international students in the United States shifted during the double stigmatization. The researcher conducted a total of 3 rounds of interviews with 15 Chinese international students who studied in the United States and returned to China between 2018 and 2020, which culminated in 45 interviews through a longitudinal study to probe the transnational identities of this population before and during the double stigmatization; the study also examined how Mindsponge Mechanism worked during the identity shifts and the interplay among stigmatization, transnational identity shifts and Mindsponge Mechanism. The study concluded that before COVID-19, Chinese international students had been stigmatized in both China and the United States. And there were three identity clusters for international students’ transnational identity: homestayers, wayfarers, and navigators based on four dimensions: intercultural competence, relocation of locality, diaspora consciousness, and attachment between the China and the US. The study concluded that during the double stigmatization, Chinese international students in all three identity clusters took individualism into their core values, whereas Chinese traditional values, such as nationalism, collectivism, and obedience to authority waned. In addition, the study corroborated the trust evaluator’s gatekeeper role and substantiated the validity and effectiveness of cost-benefit analysis on an individual’s decision to accept or reject new information and values.